Gastroesophageal reflux disease and risk of incident lung cancer: A large prospective cohort study in UK Biobank. - Ye Liao; Yunfeng Zhou; Xiaorui Zhou; Jing Chen; Zhenhua Chen; Juan Liao; Lu Long (PLoS ONE)
Background Some pathogenic mechanisms suggest a potential relationship between gastroesophageal reflux disease (GERD) and respiratory diseases. However, evidence regarding the association between GERD and lung cancer is mixed. We aim to explore this relationship based on data from the large-scale UK Biobank study. Materials and methods We performed a cross-sectional and prospective cohort study in 501,569 (45.58% male) individuals included in the UK Biobank at baseline (2006-2010). The Cox proportional hazards model and logistic regression models were used to assess the relationship between GERD and lung cancer, small cell lung cancer (SCLC), lung squamous cell carcinoma (LUSC), and lung adenocarcinoma (LUAD). Results During a mean follow-up of 11.54 years, 3,863 (0.84%) incident lung cancer cases were identified. In the cross-sectional analysis using logistic models, significant associations were found between GERD and prevalent lung cancer cases (odds ratio [OR] = 1.87, 95% confidence interval [95% CI]: 1.45-2.38) and subtypes of lung cancer, with an OR (95% CI) of 3.19 (1.47-6.79) for SCLC, 2.08 (1.33-3.21) for LUSC, 1.85 (1.15-2.91) for LUAD. In the follow-up analysis using Cox models, GERD was associated with an increased risk of lung cancer (hazard ratio [HR] = 1.24, 95%CI: 1.14-1.34). Similar associations were also observed between GERD and SCLC (HR = 1.39, 95% CI: 1.09-1.78), LUSC (HR = 1.40, 95% CI: 1.18-1.65), and LUAD (HR = 1.17, 95% CI: 1.02-1.33). The risk of lung cancer resulting from GERD was mainly elevated in former smokers (HR = 1.38, 95% CI: 1.23-1.54) and current smokers (HR = 1.18, 95% CI: 1.04-1.34), but not in never-smokers (HR = 0.89, 95% CI: 0.70-1.14). No significant association was observed in former smokers who had quit smoking for at least 25 years. Conclusions We found that GERD was positively associated with an increased risk of lung cancer, especially among smokers. Awareness of this association may be beneficial for prevention and treatment strategies of both diseases.